Can specially trained community care workers effectively support patients and their families in the home setting at the end of life?. (21st November 2017) - Poulos, Roslyn G.; Harkin, Damian; Poulos, Christopher J.; Cole, Andrew; MacLeod, Rod
Abstract: Surveys indicate that many Australians would prefer to die at home, but relatively few do. Recognising that patients and their families may not have the support they need to enable end‐of‐life care at home, a consortium of care providers developed, and received funding to trial, the Palliative Care Home Support Program (PCHSP) across seven health districts in New South Wales, Australia. The programme aimed to supplement end‐of‐life care in the home provided by existing multidisciplinary community palliative care teams, with specialist supportive community care workers (CCWs). An evaluation of the service was undertaken, focussing on the self‐reported impact of the service on family carers (FCs), with triangulation of findings from community palliative care teams and CCWs. Service evaluation data were obtained through postal surveys and/or qualitative interviews with FCs, community palliative care teams and CCWs. FCs also reported the experience of their loved one based on 10 items drawn from the Quality of Death and Dying Questionnaire (QODD). Thematic analysis of surveys and interviews found that the support provided by CCWs was valued by FCs for: enabling choice (i.e. to realise end‐of‐life care in the home); providing practical assistance ("hands‐on"); and for emotional support and reassurance. This was corroborated by community palliative care teams and CCWs. Responses by FCs on the QODD items indicated that in the last week of life, effective control of symptoms was occurring and quality of life was being maintained. This study suggests that satisfactory outcomes for patients and their families who wish to have end‐of‐life care in the home can be enabled with the additional support of specially trained CCWs. A notable benefit of the PCHSP model, which provided specific palliative care vocational training to an existing community care workforce, was a relatively rapid increase in the palliative care workforce across the state.